Haikyu!!. 5, Inter-high begins! - Furudate, Haruichi, 1983- (Shonen Jump manga., 2016)
Seeing "the Little Giant" compete in the national volleyball finals has inspired Shoyo Hinata to be the best volleyball player he can be. Now Karasuno faces two of the top four schools in their inter-high qualifiers bracket, and their confidence is shaken after losing all their practice games against Nekoma. They'll have to step up their teamwork if they hope to move on to the finals.